An assessment of e-service quality, e-satisfaction and e-loyalty: Case of online shopping in Pakistan. (2nd October 2019) - Khan, Mukaram Ali; Zubair, Syed Sohaib; Malik, Maria
Abstract : Purpose: The purpose of this paper is to examine e-service quality (E-SQ) of online shopping in Pakistan using "E-S-QUAL scale." Moreover, in this study, the relationship of E-SQ with e-customer satisfaction (E-CS) and e-customer loyalty (E-CL) has been studied. Design/methodology/approach: Following a quantitative research methodology, data were collected from 298 respondents using convenience sampling and survey research design was followed. In order to develop the model and test the hypotheses, structure equation modeling (SEM) was done through AMOS. Findings: Findings indicate that all of the first latent constructs are significant where E-CS and E-CL (dependent variables) are influenced by E-SQ (independent variable). Using SEM, statistically fit structural model was developed on the basis of confirmatory factor analysis. The analysis shows that there is a strong positive relation between E-SQ and E-CS and E-SQ and E-CL. Practical implications: Asian markets have been identified as the fastest growing e-commerce markets in present era. Similarly, retail sector in Pakistan is booming, at the same time an exponential increase is being observed in the number of internet users and online shopping. It is important for marketers and retailers to explore new horizons and enter the age of e-commerce for expansion of their businesses. Originality/value: The increasingly wide use of the internet is influencing everything around the globe and these emerging e-commerce trends have tremendously changed the mode of shopping from brick and mortars to e-stores. The study explores the e-commerce and focuses on E-SQ and its impact on E-CS and E-CL in the context of a developing economy, i.e. Pakistan, uncovering the key dimensions and attributes.